Evaluación del comportamiento fenológico y rendimiento de cuatro híbridos de maíz duro amarillo a dos niveles de fertilización, en el cantón Pindal de la provincia de Loja - Granda Samaniego, Diego Alexander (2021)
The cultivation of corn (Zea mays) is one of the most widespread and ancient in the world, originating in Mexico, where it has coexisted with different species of the genus Zea (FAO, 2018). Currently there are many hybrids developed, but not all of them are adapted to the different conditions that exist in the corn areas of the Loja province, which is why the need arises to evaluate the yield and establish the best genetic material for the purposes of future recommendations, the The objective of this research was to evaluate the phenological and productive behavior of four hard yellow corn hybrids against the application of two levels of fertilization in the Pindal canton. The hybrids DK 7088, SOMMA, NS 82, DK 7500, provided by the Ecuaquímica company and are commercialized in the research area were used. The test was implemented in the “Guácimo” neighborhood, Milagros parish of Pindal canton, Loja province with a DBCA using two levels of fertilization (traditional F1 and Ecuachemical F2), for each hybrid giving a total of eight treatments and four repetitions giving a total of 32 EU, taking the data every week until flowering. Throughout the crop cycle the average temperature of each day was taken, the variables such as leaf area, length and stem diameter were taken weekly, then at harvest representative samples of each UE were taken, measuring number of rows, length and diameter of ears, gross weight and bulk weight, to estimate the production of each treatment. The SOMMA hybrid, regardless of its fertilization level, had a smaller leaf area, greater precocity, reaching R1 in 54 DDS. Regarding production, the hybrid that showed the best performance was NS 82 with 8668.5 kg ha-1 (F2) and the hybrid with the lowest yield in both fertilizations was SOMMA with 5118 kg ha-1 (F1) and 5337, 5 kg ha-1 (F2), also hybrids 7088 and 7500 in traditional fertilization (F1), maintain an average production of 7138 Kg ha-1. Keywords: corn, hybrid, fertilization, production.